2012
DOI: 10.1016/j.jmu.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Three-dimensional Ultrasound Applications in Fetal Growth Restriction

Abstract: KEY WORDSfetal growth restriction, three-dimensional ultrasound Fetal growth restriction (FGR), previously known as intrauterine growth restriction, remains one of the main challenges in maternity care. Three-dimensional ultrasound (3DUS) has the potential to provide improved visualization of the fetal anatomic morphology compared with conventional two-dimensional ultrasound imaging. The present paper reviews 3DUS studies in the diagnosis, evaluation and prediction of FGR, and discusses the possible clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The prenatal diagnosis uses various non-invasive and invasive techniques to provide early information of any abnormality in a foetus [1]. Three-dimensional (3D) ultrasonography is the mainstay for foetal examination and detection of any abnormalities as early as possible [2]. The results of this examination are variable depending on the time of examination and the expertise of the examiner.…”
Section: Introductionmentioning
confidence: 99%
“…The prenatal diagnosis uses various non-invasive and invasive techniques to provide early information of any abnormality in a foetus [1]. Three-dimensional (3D) ultrasonography is the mainstay for foetal examination and detection of any abnormalities as early as possible [2]. The results of this examination are variable depending on the time of examination and the expertise of the examiner.…”
Section: Introductionmentioning
confidence: 99%
“…Using this same principle can also be designed fetal monitors, using an FM demodulator, which allows sound to play in terms of the movements of the heart and the body of the baby [82] [83] [84] [85] [86], in the same way it can build an equipment to detect movement within the body to establish whether or not exist a pathological state [87], this is the foundation of electronic stethoscope [88]. However, ultrasound images have the problem of limiting the comparison of two sequences from two or more means [89], but compressing and stacking transforming congruently with multivariate analysis techniques this defect can be corrected allowing the detection, visualization, comparison and quantification of the dynamic between muscle skeleton movements, which has a high potential in pediatric patients [90] …”
Section: Introductionmentioning
confidence: 99%
“…To date, ultrasound is one of the most important tools in prenatal diagnosis of FGR or IUGR. In this special issue, Lee et al [8] review the recent literature on the prenatal assessment of FGR or IUGR by using various modes of 3D ultrasound.…”
mentioning
confidence: 99%
“…After a thorough review of the recent literature, Lee and coworkers [8] have concluded that 3D ultrasound has the potential to provide improved visualization of fetal anatomical morphology compared with conventional 2D ultrasound imaging. However, they have also pointed out that, although no preferred method for the 3D ultrasound estimation of fetal weight has emerged for prenatal diagnosis of FGR [8], the advent of 3D ultrasound imaging has allowed the accurate and reliable calculation of fetal organ and soft tissue volumes.…”
mentioning
confidence: 99%
See 1 more Smart Citation